Prospective Internet Running Under an In Band Full Duplex Scheme Based on Quantum Mechanics - Nieto-Chaupis, Huber (2020)
Once quantum computer is running it is possible to expect that more quantum computers are interconnected in the same manner as the classical ones, so that Internet is seen as an imminent task in these advanced devices. As in classical machines, the well-known In-Band-Full-Duplex (IBFD) technique can be applied in order to enhance performance. However, quantum computers depend strongly on field interaction as the responsible to achieve Rabi transitions. Using the Quamtum Fourier transformation we interpret the resulting equations in terms of the Hamiltonian action.